1970
DOI: 10.1128/aem.20.1.78-84.1970
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clostridia by Gas Chromatography: Differentiation of Species by Trimethylsilyl Derivatives of Whole-Cell Hydrolysates

Abstract: Trimethylsilyl (TMS) derivatives prepared from whole-cell hydrolysates of 36 strains, representing 10 species of Clostridium were examined by gas-liquid chromatography (GLC). The TMS profile of each species contained a group of peaks which characterized the species. Variation among strains within a species was much lower than variation between species. Some of the closely related clostridia could be differentiated by comparing their TMS profiles. Strains of Clcstridium botulinum were distinguished from C. spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1971
1971
1995
1995

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…11, lanes 8 through 13) and absent in the toxic strains. Farshy and Moss (8) reported that C. sporogenes and proteolytic strains of C. botulinum also can be differentiated by gas chromatographic patterns of trimethylsilyl derivatives of whole cell hydrolysates. Because type G (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…11, lanes 8 through 13) and absent in the toxic strains. Farshy and Moss (8) reported that C. sporogenes and proteolytic strains of C. botulinum also can be differentiated by gas chromatographic patterns of trimethylsilyl derivatives of whole cell hydrolysates. Because type G (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the gas-liquid chromatographic profiles of whole-cell hydrolysates were nearly identical. Intraspecies similarities in derivative patterns have been shown to be characteristic of some bacterial species (2,8,9,22).…”
Section: Discussionmentioning
confidence: 99%
“…The three other approaches involve a chromatographic characterization of structural components. They use either derivatives of extracted cellular components (1,7,21,22), derivatives of whole cell hydrolysates (8,9,12,13), or the separation of pyrolytically induced molecular fragments (5,18). The gas chromatograph can make the characterization of a variety of microorganisms both rapid and simple.…”
mentioning
confidence: 99%